DAMPAK PARIWISATA TERHADAP KEHIDUPAN MASYARAKAT LOKAL DI KAWASAN WISATA (Desa Ciburial Kabupaten Bandung) - Annisa Lazuardina; Shabrina Amalia Ghassani (Warta Pariwisata, 2023)
Ciburial Village is one of the tourist villages in Bandung Regency, with several tourist attractions such as the Juanda Forest Park, the Keraton Cliff, Dutch Cave, Japanese Cave, and cafes scattered throughout the Ciburial Village area. The mushrooming of these cafes is due to the strategic location of Ciburial Village and high demand, this has resulted in the conversion of agricultural land into commercial buildings. The land function change has an impact on the lives of the people of Ciburial Village. This study aims to identify the factors that influence the impact of tourism and analyze the impact of tourism on socio-cultural and economic aspects of the life of the people of Ciburial Village. This research is descriptive with a qualitative approach. Data collection is done by means of observation, interviews, and secondary data from the internet or related agencies. The analysis in this study uses data reduction, data presentation, and conclusions.